Magnetic Fluid Infiltrated Microbottle Resonator Sensor With Axial Confined Mode - Fengyu Hou; Xiaobei Zhang; Zijie Wang; Lei Yang; Wen Sun; Yong Yang; Yanhua Dong; Yi Huang; Tingyun Wang (IEEE Photonics Journal)
We report a magnetic field sensor based on an optofluidic microbottle resonator (OFMBR) with whispering gallery mode (WGM) strongly confined in the axial direction, with the hollow core inherently easy to infiltrate the magnetic fluid. The device is simply fabricated along a silica capillary through a fusing splicer. And the influence of number of discharges on the size of the device is analyzed according to the state equation of ideal gas, which is verified by experimental results. In the magnetic field range from the critical value (40 Gs) to the saturated value (300 Gs), the resonant wavelength shifts linearly with the increase of magnetic field strength, with a sensitivity of 8.45 pm/Gs demonstrated, based on the axial confined mode of OFMBR with a Q-factor of 1.28 × 106. This sensor possesses advantages of simple structure, easy fabrication process, and compact size for magnetic field sensing.